Prevalence of menopausal symptoms and perceptions about menopause among postmenopausal women attending Gynaecology OPD at GMC Idukki, India - Joseph, Leena A.; Varghese, Acka Priya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Idukki is a hilly tract area in the state of Kerala. No studies regarding menopause has been reported from Idukki. This study is done among postmenopausal women in an attempt to shed light on the prevalence of menopausal symptoms and perceptions of postmenopausal women in a panchayat in Idukki district which is typically a rural area. Primary objectives of the study were to find the prevalence of menopausal symptoms in post-menopausal women attending the outpatient department of Government Medical College, Idukki, India and to find the perceptions about menopause among these post-menopausal women. Secondary objectives were to find the mean age and pattern of attainment of menopause among postmenopausal women and to find the treatment seeking behavior of the post-menopausal women residing in this area. Methods: A cross-sectional observational study is done among 100 postmenopausal women attending the outpatient department of Obstetrics and Gynaecology. Questions are asked based on interview schedule. The results are then analyzed. Results: The mean age of menopause was 45.69± 4.35. 78% of population had one or more symptoms in the menopausal period. Only 19.5% of the symptomatic women took treatment. 77% had positive perceptions. Conclusions: The awareness of these women in this area is poor thus limiting the treatment seeking behavior. Improvement of awareness is a must to improve the quality of life of post-menopausal women.